FACTORS AFFECTING PROCUREMENT PERFORMANCE IN NON-GOVERNMENTAL ORGANIZATION IN ZAMBIA - Chifuti, Chipepo; Kasongo, Richard Mwale (International Journal of Supply Chain Management, 2020)
Purpose:The main objective of the study was to establish the factors affecting procurement performance at PATH. The study was conducted to examine the impacts of staff qualification, information and communication technology, procedure and departmental collaboration on procurement performance. Methodology: Study Design:Mixed Methods was used , sampling technique was Stratified random sampling. Primary data was collected using questionnaire. Descriptive and inferential data analysis methods were used. All respondents filled in and returned the questionnaire, making the response rate 100%.The study conducted a multiple regression analysis to determine the influence of the independent variables on procurement performance sample population , top level manager, technical team (requester), procurement staff and all PATH employees and Sample Size 42 respondents from PATH. Findings: The study found that The two factors that showed significant effect on procurement performance are Information and communication technology with p=0.018 and departmental collaboration with the p-value of 0.001 (p< 0.05). Furthermore, the Pearson Correlation Coefficient computed and tested at 1% significance level indicated that there is a strong positive relationship (r=0.716) between departmental collaborative and procurement performance. The relationship was statistically significant at 1% level (p=0.000, <0.01) Based on the ANOVA, the significance value 0.000 is less than 0.05 thus the model is statistically significant in predicting how the independent variables influence the procurement performance at PATH. The F critical at 5% level of significance was 2.68. The F calculated from the ANOVA table is 5.455, which is greater than the F critical (2.68). This shows that the overall model was significant.From the research findings most of the respondents indicated that the most important factor is departmental collaboration followed by information communication and technology. The other two independent variables, staff qualification and procurement procedures, showed an insignificant relationship with procurement performance at PATH. Unique contribution to theory, practice and policy: The study recommends that there is need of Staff awareness through training should be carried out to achieve superior knowledge in entire procurement process at PATH. NGOs need to embrace ICT in their procurement systems in order to achieve transparency as this reduces physical contact with vendors in solicitation of procurement document